Answer:
The 6th degree polynomial is [tex]p(x) = (x-1)^3(x-4)^2(x+3)[/tex]
Step-by-step explanation:
Zeros of a function:
Given a polynomial f(x), this polynomial has roots [tex]x_{1}, x_{2}, x_{n}[/tex] such that it can be written as: [tex]a(x - x_{1})*(x - x_{2})*...*(x-x_n)[/tex], in which a is the leading coefficient.
Zero 1 with multiplicity 3.
So
[tex]p(x) = (x-1)^3[/tex]
Zero 4 with multiplicity 2.
Considering also the zero 1 with multiplicity 3.
[tex]p(x) = (x-1)^3(x-4)^2[/tex]
Zero -3 with multiplicity 1:
Considering the previous zeros:
[tex]p(x) = (x-1)^3(x-4)^2(x-(-3)) = (x-1)^3(x-4)^2(x+3)[/tex]
Degree is the multiplication of the multiplicities of the zeros. So
3*2*1 = 6
The 6th degree polynomial is [tex]p(x) = (x-1)^3(x-4)^2(x+3)[/tex]